Laser fabrication of all-solid-state microsupercapacitors with ultrahigh energy and power based on hierarchical pore carbon. (March 2016) - Huang, Hsin-Chieh; Chung, Chung-Jen; Hsieh, Chien-Te; Kuo, Ping-Lin; Teng, Hsisheng
Abstract: Microsupercapacitors (MSCs) are used as power sources or energy storage units in microelectronic devices. This study fabricates all-solid-state MSCs using a laser for the micromachining of substrates coated with activated mesophase pitch (aMP) to produce in-plane interdigitated microelectrodes for use in conjunction with gel-state electrolytes. Due to the inclusion of hierarchically-connected micropores and mesopores, aMP carbon has considerable capability for charge storage and the delivery of energy at high rates. Through reduction in the finger width, the proposed laser-patterned design substantially reduces the resistance to ion drift in the electrolyte bulk and ion diffusion across the carbon-film network. The use of an ionogel enables the MSC to reach stack capacitance of 12 F cm −3, stack energy of 16 mW h cm −3, and stack power of 160 W cm −3 . These energy and power values approach those obtained from thin-film lithium ion batteries and aluminum electrolytic capacitors, respectively; this synergy between high energy and power is unprecedented for MSCs. The proposed MSCs exhibit outstanding cycling stability and those using ionogel present high thermal stability. The proposed fabrication methods enable the on-chip integration of microelectronic devices and therefore provide an opportunity for the development of a variety of micro/nano-sized energy devices. Graphical abstract: All-solid-state microsupercapacitors are fabricated using a laser writer to produce in-plane interdigitated microelectrodes, activated mesophase pitch with hierarchical pore structure as the electrode material, and hydrogel and ionogel as the electrolytes. The microsupercapacitors show ultrahigh stack volumetric energy and power, which are comparable to to those of Li-ion thin film batteries and aluminum electrolytic capacitors, respectively. Highlights: Laser micromachining enables lithography-free and on-chip fabrication. This work incorporates carbon porosity with electrode architecture for capacitors. The all-solid-state capacitors exhibit outstanding cycling and thermal stabilities. Energy and power reach those of thin-film Li-battery and electrolytic capacitor.